2023
DOI: 10.1093/jacamr/dlad060
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profiles of Escherichia coli isolated from laying hens in Zambia: implications and significance on one health

Steward Mudenda,
Sydney Malama,
Musso Munyeme
et al.

Abstract: Background Antimicrobial resistance (AMR) has been deepening in the layer poultry sector in Zambia partly due to the inappropriate use of antimicrobials. Escherichia coli (E. coli), a commensal and zoonotic bacterium, can potentially be a source of AMR. Objectives This study assessed the phenotypic AMR profiles of E. coli isolated from the apparent health-laying hens in Lusaka and Copperbelt provinces of Zambia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 114 publications
2
13
0
Order By: Relevance
“…After con rmation, the isolates were subjected to antimicrobial susceptibility testing. These isolates were then preserved and kept at 20°C for storage [11].…”
Section: Isolation and Biochemical Methodsmentioning
confidence: 99%
“…After con rmation, the isolates were subjected to antimicrobial susceptibility testing. These isolates were then preserved and kept at 20°C for storage [11].…”
Section: Isolation and Biochemical Methodsmentioning
confidence: 99%
“… 34–36 This has been demonstrated by an increased number of pathogens that have developed resistance to antimicrobials, some of which are of human priority. 37–41 …”
Section: Introductionmentioning
confidence: 99%
“… 94 , 104–108 Consequently, there is evidence of antimicrobial-resistant pathogens across the human and animal sectors. 37 , 38 , 41 , 99 , 109–115 A study by Masich et al 116 revealed that about 67% of antimicrobials were inappropriately prescribed to non-critically ill adult patients admitted to the University Teaching Hospital in Lusaka, Zambia. Intriguingly, the Zambian government has put in measures to promote the appropriate use of antibiotics by developing and implementing the National Action Plan (NAP) on AMR.…”
Section: Introductionmentioning
confidence: 99%
“…One health is not modern as it recognizes closely linked interconnection among animal, human, plant, and ecological health ( Mudenda et al, 2023 ). However, one health received renewed attention due to the increasing rate and dangerousness of threats associated with animals, humans, plants, and the environment ( Badr et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%